Tingkat Kesehatan Keuangan Organisasi Pengelola Zakat Di Indonesia - Siti Aminah Anwar; Anik Malikah (JAS (Jurnal Akuntansi Syariah), 2021)
As the largest Muslim country in the world, Indonesia has great potential in collecting zakat, infaq, alms, and waqf funds (ZISWAF) to alleviate poverty and social inequality. This study aims to demonstrate the financial health or performance of the zakat management organization (ZMO) by analyzing the ratio of activity, efficiency, amil, liquidity, and growth based on the provisions of the strategic study centre the national amil zakat agency (Puskasbaznas). This study uses a sample of twenty financial statements from five ZMO published from 2015-2018. This study uses an explanatory research method with a quantitative descriptive approach. The results show that the financial statements of the ZMO have implemented PSAK 45 and PSAK 109. The financial health or performance of the ZMO is categorized as quite reasonable. Then the efficiency ratio affects the financial health or performance of ZMO. In contrast, the ratio of activity, amil, liquidity, and growth do not affect the financial health or performance of ZMO. The results of this study are able to detect ZMO who do not aim to make a profit. Then it is used as a reference for ZMO in improving financial health or organizational performance.